Dog man lord of the fleas Vol. 5 - Pilkey, Dav (New York, NY Graphix, 2018)
When a new bunch of baddies bust up the town, Dog Man is called into action -- and this time he isn't alone. With a cute kitten and a remarkable robot by his side, our heroes must save the day by joining forces with an unlikely ally: Petey, the World's Most Evil Cat. But can the villainous Petey avoid vengeance and venture into virtue?
2
Keywords: Dogs -- Comic books, strips, etc -- Juvenile literature; Police -- Comic books, strips, etc -- Juvenile literature